Pembuatan Na2O/Serbuk Besi Sebagai Katalis Pada Proses Transesterifikasi Minyak Sawit Off Grade Menjadi Biodiesel - Hanafi, Muhammad Rifter; Helwani, Zuchra; Saputra, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Heterogeneous solid base catalyst synthesized with iron powder to load sodium oxide through impregnation and calcination method. The optimum conditions for the manufacture of catalysts investigated. Effect of weight ratio of Na2O to iron powder and calcination temperature on the catalytic performance were studied. The catalyst with the highest activity is obtained when the weight ratio of Na2O to iron powder is 70:30 and calcination temperature of 550 °C under transesterification reaction conditions of a molar ratio of methanol : oil 8:1, catalyst dosage of 2% by weight, temperature of 60 °C for 3 hours with biodiesel results reached 86.40%.Keywords : biodiesel, calcination, catalysts, impregnation, iron powder, sodium oxide, transesterification.